2017
DOI: 10.1177/0969733017712082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived organizational justice and moral distress in intensive care unit nurses

Abstract: According to the results of the study, there was a reverse significant relationship between moral distress and perceived organizational justice; therefore, the head nurses are expected to contribute to reduce moral distress and to increase perceived organizational justice in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 37 publications
7
51
0
2
Order By: Relevance
“…In this context, Haghighinezhad et al 20 recommended that certain managerial strategies need to be adopted such as optimization of effective communication skills, changing of attitude toward nurses, and paying more attention to their opinions. Increasing the reward, revision of procedures and guidelines, and reducing work hours could be useful in the long run for the health of nurses and the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, Haghighinezhad et al 20 recommended that certain managerial strategies need to be adopted such as optimization of effective communication skills, changing of attitude toward nurses, and paying more attention to their opinions. Increasing the reward, revision of procedures and guidelines, and reducing work hours could be useful in the long run for the health of nurses and the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, findings reported by Fathabad et al 26 and Ito et al 27 estimated the mean of the perceived organisational justice to be higher than average. Also Mohamed et al 2 illustrated that nurses had a moderate level of perceived organisational justice, while Haghighinezhad et al 20 indicated that nurses rated organisational justice as low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be ascribed to the fact that the nurses are pleased about their work environment, they willingly work in an HD unit, their OJ scores are above the average, the organısatıons support the nurses in their application to get a dialysis certificate, and they have no difficulty in getting supplies in the workplace. There's a negative correlation between OJ and EE, anxiety, work stress, depression and moral distress (Elovainio et al ; Laschinger ; Haghighinezhad et al ; Top & Tekingündüz ), whereas there's a positive significant correlation between JS and ORGANISATIONAL commitment and trust (Top ).…”
Section: Discussionmentioning
confidence: 99%